THE EFFECTS OF EARNING PER SHARE, DEBT TO EQUITY,RETURN ON ASSET AND NET PROFIT MARGIN ON STOCK PIECES (A STUDY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FROM 2018-2021) - Yulianti Anggrahini Dewi; Hadi Samanto; Suprihati Suprihati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to determine the effects of earning per share, debt to equity, return on asset, and net profit margin on stock prices (A study on manufacturing companies listed on the Indonesia Stock Exchange from 2018-2021). The factors tested in this study are earning per share, debt to equity, return on asset, and net profit margin. Data collection in this study used the documentation method, which involved written data related to the tested factors and stock prices from 2018-2021. The data analysis method used in this study was multiple linear regression analysis with a significance level of 5% or 0.05. The results of the study prove that the earning per share variable with a significance value of 0.000 < 0.05, return on asset 0.001 < 0.05, and net profit margin 0.002 < 0.05 have an effect on stock prices in manufacturing companies listed on the Indonesia Stock Exchange. On the other hand, the debt to equity variable does not have an effect on stock prices in manufacturing companies listed on the Indonesia Stock Exchange, as indicated by the t-test results above 5%. The results of the F-test show that the variables earning per share, debt to equity, return on asset, and net profit margin collectively have an effect on dividend policy with an R2 value of 64.2%. Keywords: Earning Per Share, Debt to Equity, Return on Asset, Net Profit Margin, Stock Prices